PENERAPAN MODEL PROJECT-BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GAMBAR KONSTRUKSI BANGUNAN DI SMKN 6 BANDUNG - Wijayanti, Subekti Dwi (2017)
Model pembelajaran yang saatinidilakukan di dalamkelasmasihmenggunakan model pembelajarankonvensional.Secaraumum, model pembelajaraninilebihberpusatkepada guru dengankomunikasilebihbanyaksatuarahdari guru kesiswa.Siswakurangberperanaktifselama proses pembelajaranmenyebabkankurangnyapemahamandanketerampilansiswamengenaimateripelajaran. Sebagianbesarsiswakesulitanmenyelesaikantugasgambar yang diberikandanberdampakpadaketerlambatanpengumpulantugasdanpenurunanhasilbelajar.Upayauntukmengatasimasalahtersebutadalahdenganmenerapkan model project-based learningsebagaialternatif yang dapatmembuat guru dansiswabersama-samaberperanaktifdalammemecahkanpermasalahan yang terjadi di dalamkelas.SehinggadapatmendukungtujuanpenelitianyaitumeningkatkanhasilbelajarsiswapadamatapelajaranGambarKonstruksiBangunan. Metodepenelitian yang digunakanyaituPenelitianTindakanKelas model Kemmis& Mc. Taggart. Penelitiandilakukansebanyaktigasiklus, setiapsiklusterdiridariperencanaan, pelaksanaan&pengamatan, danrefleksi.Hasilpenelitianmenunjukkanadanyapeningkatanhasilbelajarsiswa, hal ini terbukti dengan meningkatnya persentaseketuntasanbelajarsiswapada setiap siklusnya.Padasiklus 1, persentaseketuntasanbelajarsiswapadaranahkognitifsebesar 42% sedangkanpadaranahpsikomotoriksebesar 57%.Padasiklus 2, persentaseketuntasanbelajarsiswameningkatpadaranahkognitifmenjadi 67% sedangkanpadaranahpsikomotorikmenjadi 72%.Padasiklus 3, persentaseketuntasanbelajarsiswaterusmeningkatpadaranahkognitifmencapai 91% sedangkanpadaranahpsikomotorikmencapai 88%.Dengan demikian dapat disimpulkan bahwa penerapan model Project-Based Learning mampu meningkatkanhasilbelajarsiswapadamatapelajaranGambarKonstruksiBangunan di SMKN 6 Bandung. Kata kunci: Model Pembelajaran, Project Based Learning, HasilBelajar, RanahKognitifdanPsikomotorik;--- The current learning models used in the classroom still use the conventional learning model. In general, this learning model is more teacher-centered with more one-way communication from teacher to student. Students play less active role during the learning process causing lack of understanding and skill of students about subject matter. Most of students have difficulty in completing the drawing tasks and have an impact on the delay in collecting tasks and decreasing learning outcomes. One of the ways to overcome these problems is to apply the project-based learning model as an alternative that can make teachers and students together play an active role in solving problem occurring in the classroom. Hopefully it can support the purpose of research to improve students' learning outcomes on the subject of building construction drawing. The research method uses class action research model of Kemmis& Mc. Taggart. It was conducted in three cycles. Each cycle consisted of planning, implementation & observation, and reflection. It indicates an increase in students' learning outcomes. It was proved by increasing the percentage of students learning mastery in each cycle. In cycle 1, the percentage of students learning mastery in the cognitive domain was 42%, and the psychomotor domain was 57%. In cycle 2, the percentage of students learning mastery increased in the cognitive domain to 67%, and the psychomotor domain to 72%. In cycle 3, the percentage of students learning mastery increased more in the cognitive domain until 91% while in the psychomotor domain until 88%. Therefore it can be concluded that the implementation of project-based learning model can improve students' learning outcomes in the subject of building construction drawing at vocational high school 6 Bandung. Keywords : Learning Model, Project Based Learning, Learning Outcomes, Cognitive and Psychomotor Domain